Memoir, Correspondence, and Miscellanies, From the Papers of Thomas Jefferson, Volume 2 - Jefferson, Thomas, 1743-1826; Randolph, Thomas Jefferson, 1792-1875 (Salt Lake City, UT : Project Gutenberg, 2005)
"Memoir, Correspondence, and Miscellanies, From the Papers of Thomas Jefferson" edited by Thomas Jefferson Randolph is a historical account written in the early 19th century. The work comprises a collection of letters and correspondence authored by Thomas Jefferson during his political career, primarily focusing on American diplomatic relations and interactions with foreign nations in the late 18th century. The content explores themes of governance, international trade, and Jefferson$1 (Bs reflections on the evolving political landscape after the American Revolution. The opening of this collection presents a series of Jefferson's letters from London in 1786, addressed to various significant figures including Richard Henry Lee and Charles Thomson. In these letters, Jefferson discusses the challenges and sentiments surrounding American independence, emphasizing the lack of political connections with Great Britain and reflecting on the prospects of a commercial treaty. His correspondence reveals Jefferson's observations on British attitudes towards America, the unlikelihood of favorable arrangements, and the importance of establishing diplomatic ties with other nations. This initial segment sets the stage for a deeper understanding of Jefferson's political philosophy and the nascent complexities of American diplomacy during the formative years of the republic. (This is an automatically generated summary.)s
Release date is 2005-09-30
Produced by David Widger
Keywords: United States -- Politics and government -- 1775-1783; United States -- Politics and government -- 1783-1865